Mechanisms and therapeutic research progress in intestinal fibrosis - Liu, Yanjiang; Zhang, Tao; Pan, Kejian; Wei, He (Frontiers in Medicine, 2024)
Intestinal fibrosis is a common complication of chronic intestinal diseases with the characteristics of fibroblast proliferation and extracellular matrix deposition after chronic inflammation, leading to lumen narrowing, structural and functional damage to the intestines, and life inconvenience for the patients. However, anti-inflammatory drugs are currently generally not effective in overcoming intestinal fibrosis making surgery the main treatment method. The development of intestinal fibrosis is a slow process and its onset may be the result of the combined action of inflammatory cells, local cytokines, and intestinal stromal cells. The aim of this study is to elucidate the pathogenesis (e.g., extracellular matrix (ECM), cytokines and chemokines, epithelial-mesenchymal transition (EMT), differentiation of fibroblast to myofibroblast and intestinal microbiota) underlying the development of intestinal fibrosis and to explore therapeutic advances (such as regulating ECM, cytokines, chemokines, EMT, differentiation of fibroblast to myofibroblast and targeting TGF-β) based on the pathogenesis in order to gain new insights into the prevention and treatment of intestinal fibrosis